Correlation of dietary inflammation index with sarcopenia in patients with chronic kidney disease based on the NHANES database - Ma Xiao-yan; Yao Rui; Ni Lin; Dai Jing-jing (Linchuang shenzangbing zazhi)
ObjectiveTo identify the correlation of dietary inflammatory index （DII） with sarcopenia in patients with chronic kidney disease （CKD） based on the National Health and Nutrition Examination Survey （NHANES） database.MethodsData from 1999-2006 and 2012-2018 in the NHANES database were analyzed. DII was calculated from dietary data， and patients were divided into DII Q1， DII Q2， DII Q3， and DII Q4 groups based on DII quartiles. Age， gender and the prevalence of sarcopenia were compared between the groups. Logistic regression model was used to analyze the relationship between DII and sarcopenia in patients with trend and stratification analysis. Restricted cubic spline plots （RCS） were used to analyze a nonlinear relationship between DII and sarcopenia.ResultsA total of 1，660 CKD patients were included in this study. There was a significant difference in the prevalence of sarcopenia in CKD patients among the DII Q1 （42.17%）， DII Q2 （46.99%）， DII Q3 （52.05%）， and DII Q4 （58.80%） groups （χ2=25.224， P<0.001）. After adjusting for confounders， DII was still significantly associated with the risk of sarcopenia in CKD patients （OR=1.214， 95%CI： 1.135-1.299， P<0.001）. Compared with the DII Q1 group， CKD patients in the DII Q3 （OR=1.467， 95%CI： 1.106-1.948， P=0.008）， and DII Q4 groups （OR=1.876， 95%CI： 1.405-2.511， P<0.001） had a significantly higher risk of developing sarcopenia， with an increasing odds ratio （OR） （Pfor trend < 0.001）. After stratification， DII remained positively associated with the risk of sarcopenia in female CKD patients （P=0.024）.ConclusionDII is strongly associated with the risk of sarcopenia in CKD patients， with higher DII scores associated with a higher risk of developing sarcopenia.